Improved Electrical Conductivity of a Carbon Nanotube Mat Composite Prepared by In-Situ Polymerization and Compression Molding with Compression Pressure - Noh, Ye Ji; Kim, Han Sang; Kim, Seong Yun (SPRINGER JAPAN KK, 2012)
A fabrication method to improve the processability of thermoplastic carbon nanotube (CNT) mat composites was investigated by using in-situ polymerizable and low viscous cyclic butylene terephthalate oligomers. The electrical conductivity of the CNT mat composites strongly depended on the compression pressure, and the trend can be explained in terms of two cases, low and high compression pressure, respectively. High CNT mat content in the CNT mat composites and the surface of the CNT mat composites with fully contacted CNTs was achieved under high compression pressure, and direct contact between four probes and the surface of the CNT mat composites with fully contacted CNTs gave resistance of 2.1 Omega. In this study the maximum electrical conductivity of the CNT mat composites, obtained under a maximum applied compression pressure of 27 MPa, was 11 904 S m(-1), where the weight fraction of the CNT mat was 36.5%.
Keywords: MECHANICAL-PROPERTIES; INTERCALATION; PAPER